Bahaya Kesibukan dalam Pelayanan: Perspektif Lukas 10:38-42 - Lestari, Eni (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
The story of Martha and Mary in Luke 10:38-42 illustrates the differing approaches to serving God that often occur in everyday life. Martha, busy with household chores, and Mary, who chose to sit and listen to Jesus' teachings, reflect two distinct responses to the call of service. In this narrative, Jesus does not defend Martha, who feels overlooked, but rather rebukes her anxiety and emphasizes the importance of choosing the better part, which is closeness to His presence. This study uses a descriptive qualitative approach with textual analysis of the narrative in Luke 10:38-42. The primary data used is the Gospel of Luke, analyzed through a hermeneutical lens to understand the meaning and message contained in the story of Martha and Mary. The aim of this research is to explore the dangers of busyness in ministry that is not accompanied by efforts to maintain an intimate relationship with God. The findings of this study highlight three key impacts that need to be aware of: first, the emergence of excessive anxiety and stress due to fatigue; second, the occurrence of disappointment in inadequate service; and third, the loss of focus on the most important aspect of life, which is a deep relationship with God. This article suggests the importance of finding a balance between active service and spiritual closeness so that ministry remains meaningful and impactful.